Search for extremity zones with discrete mathematical analysis algorithms to identify risks when drilling based on geophysical data - Bogoutdinov Shamil; Odintsova Anastasiya; Pirogova A. (Russian Journal of Earth Sciences, 2022)
Despite the impressive list of examples of the integration of pattern recognition theory into various activities in the development of oil and gas fields, the authors propose a fundamentally new approach to the use of artificial intelligence. The paper considers in detail the algorithm for searching for extremity zones, based on discrete mathematical analysis (DMA), as applied to the problem of identifying geological hazards. The application of the method is shown on models of the physical properties of rocks reconstructed from seismic data. Potentially, it can also be applied directly to the wave seismic field to identify objects.